(untitled) (Hematology Meeting Reports, 2009)
In Follicular non Hodgkin’s Lymphoma (FL-NHL) the molecular diagnosis and monitoring of the chimeric BCL2/IgH gene generated by the t(14;18)is an important tool in the diagnostic work-up at diagnosis and during the clinical follow-up. Although the clinical significance of circulating BCL2/IgH+ cells is still controversial, the persistence of these cells after conventional or high dose chemotherapy programs correlates with a shorter clinical remission.